A formação e prática pedagógica do professor de educação física e sua contribuição para o processo de alfabetização e letramento - Malcheski, Raquel de Fátima Boza dos Santos (2018)
The research presents an investigation of qualitative nature, about the pedagogical formation and practice influence from the physical education teacher in the alphabetization and literacy process of the Primary School students’ first cycle. Considering that school’s Physical Education seeks to develop the human being on dimension, intelectual, cultural and physical and comprehending that the alphabetization and the literacy are also a part of these dimensions, it is questioned: how does the formation of the Physical Education teacher and your pedagogical practice contribute with the alphabetization and literacy process, of the Primary School students’ first cycle, inside the reality context of two schools from the Curitiba’s Education Municipal Chain? Seeking to answer that indagation, it was defined as a general objective: to analyze the pedagogical practices and initial and continuing education of the Physical Education teacher graduates contribute to the alphabetization and literacy of the Primary School students’ first cycle. For this purpose, the specific objectives are: I) To know the perception that the Physical Education teachers have about alphabetization and how is it given (or not) to the articulation between these teachers and the “literacy-teachers”; II) Verify if there is articulation between the Physical Education teacher graduates’ pedagogical practice and the alphabetization and literacy process of the Primary School students’ first cycle; III) Identify how teachers analyze their formations to act in the Primary School students’ first cycle; IV) Verify if the teachers consider the students’ sociocultural context, as a contribution for the alphabetization and literacy process. As methodical instruments, besides the bibliographic analyses, were applied questionnaires to thirty five professionals and realized six interviews with Physical Education teachers that work with the first cycle classes of two municipal schools from the Municipal Chain of Santa Felicidade’s regional cores, with the intention of obtaining bigger information of how are developed the pedagogical practices, the conceptions about the alphabetization and literacy and how does the interactions happen between the professionals and the knowledge areas in question, inside this Education Municipal Core. The results show that the Physical Education professions don’t know or don’t mention the documents that should guide your pedagogical practices and even though recognize the relevance of your work inside the school environment, it is still noticed isolated (or detached from the regent teachers and the sociocultural and social space of the students), on what says about respect to the pedagogical practices that contribute effectively with the learning process aimed to alphabetization and literacy.